Trends in bank credit and finance - Nederlandse Bankiersvereniging (The Hague : Published for the Nederlandse Bankiersvereniging by M. Nijhoff, 1961)
The importance of monetary equilibrium for the regular and most efficient development of the world's resources and for a just distribution of manufactured products
"Lectures delivered ... September 1960."
Includes bibliographical references.
obn21/01/2019
Loans
Keywords: Credit; Banks and banking